On-the-job search, precationary savings and the progressivity of income taxes - Moon, Sungwon (2021)
This paper analyzes the effects of income taxation on the behaviors of workers and firms, and the equilibrium distribution of workers across income and wealth. The model extends the strand of literature that integrates an equilibrium model of job search into an incomplete market model of consumption and savings. It thus incorporates firm heterogeneity, endogenous wage offer of firms, as well as endogenous job search effort and savings of workers. The effects of income taxes ripple through the search and savings behaviors of workers, and the consequent response of the wage offer, which leads to additional changes in the search and savings of workers. In the simulations across the different tax schemes, a higher tax progressivity is shown to depress the motive of job search and precautionary savings and the wage offer of firms, leading to the lower average wage rates and the higher interest rate.